Towards strategic planning for building land information system in Nepal - Tuladhar, Arbind Man; B.C., Krishna Raj; Budhathoki, Nama Raj (Journal on Geoinformatics, Nepal, 2003)
The interaction of human societies with land is becoming crucial for the economic, social, political and environmental development. In Nepal, the main causes for the increased scarcity of land and destruction of natural resources (deforestation & degradation of agricultural land) and increasing uncontrolled urbanization are mainly due to the rapid population growth and high migration from rural to the urban and terai (i.e. flat/ plains). For managing and controlling the use of land and resources, a reliable land information system (LIS) is a prerequisite. Recently HMG Ministry of Land Reform and Management (MLRM) has established “Department of Land Information and Archive (DoLIA)” as a new dedicated department. The main tasks are to build and maintain a nation-wide LIS for timely supply of reliable land information to all its users at an affordable cost. Since such tasks are complex in nature, time consuming and costly, it requires the realistic strategies to carry out its tasks. This paper overviews the effort that has been put for the last nine years to build LIS in Nepal. It then provides an approach to continue the effort by formulating a strategic plan for the DoLIA within internal and external environmental constraints. To support such formulation, the situation analysis with respect to strengths, weakness, opportunities and threats are performed. The paper then presents a broad LIS vision and various strategies to meet in a planned time with the effective utilization of resources.